The Brasilia Rules - Goldman, Diego Hernán (2020)
In this paper, the Brasilia Rules are analyzed as an effective instrument to reduce different types of costs that operate as extrinsic and intrinsic barriers to access to justice by individuals in vulnerable situations. In this sense, they contribute to the efficiency of the legal system and to the maximization of welfare and social wealth, which is a valuable contribution to social cohesion, to the realization of life projects of people, to the prosperity and to the full development of large sectors of the population of our historically relegated countries.